Physico-chemical characterization of Anopheles gambiae s.l. breeding sites and kdr mutations in urban areas of Cotonou and Natitingou, Benin - Djegbe, I.; Hessou-Djossou, D.; Boukari, M.Y.G.; Nonfodji, O.; Tchigossou, G.; Djouaka, R.; Cornelie, S.; Akogbeto, M.; Djogbenou, S.L.; Chandre, F. (2024)
Background This study aimed to investigate the relationship between the physicochemical characteristics of An. gambiae s.s. and An. coluzzii breeding sites, the susceptibility profiles to commonly used insecticides in public health, and the underlying insecticide resistance mechanisms.